A game-theoretic analysis of production and coordination under combined carbon policies - Ao Qiao; Siyu Zeng; Jianing Wang (PLoS ONE, 2026)
To mitigate the growing threat of global warming, countries have increasingly adopted carbon policies to control industrial carbon emissions. Although previous research has analysed the effectiveness of individual carbon policies, such as cap-and-trade and subsidy schemes, the combined effects of these policies remain largely unexplored. Moreover, existing studies often overlook detailed production processes, such as lot-sizing decisions, which significantly influence total emissions of the manufacturer. To bridge these gaps, this study examines the coordination between a manufacturer and a retailer under a combined carbon policy framework, incorporating both cap-and-trade and low-carbon subsidy policies. A Stackelberg game model is developed to explore the strategic decisions of supply chain members. The manufacturer’s production process is modelled using queuing theory to capture the impact of operational details on carbon emissions. Supply chain scenarios are compared and analysed under different combinations of carbon policies and contractual arrangements. The results demonstrate that a combined carbon policy can enhance both profitability and sustainability across the supply chain. Among subsidy schemes, the green investment subsidy is more effective than product subsidy in emissions reduction. Additionally, while revenue-sharing contracts yield greater emissions reductions, cost-sharing contracts offer a better balance between economic and environmental objectives. These findings offer practical implications for policymakers and supply chain managers aiming to design integrated strategies that simultaneously achieve profitability and sustainability.